The Concept of Corruption in J.G.A. Pocock's The Machiavellian Moment. Issue 2 (17th February 2017) - Sparling, Robert
SUMMARY: In the scholarship on the concept of political corruption, one frequently encounters the lamentation that the manner in which the concept is deployed in liberal modernity is insufficiently attuned to the richer sense in which the term was employed in the 'civic humanist' tradition. In these lamentations, the usual point of reference is J.G.A. Pocock's The Machiavellian Moment, a work that made corruption the central term of art in a political language stretching from the Renaissance to the eighteenth century and beyond. Certainly there is something quite attractive today about the 'Machiavellian' inflection of the term—our era is replete with the very things the protagonists of Pocock's story decried: debt, dependency, oligarchy, standing armies and the diminution of civic duties. But to what extent is Pocock's classic text a reliable guide for those studying the concept of corruption? This article suggests that Pocock uses the term in an excessively capacious manner, which both weakens his book's utility for understanding eighteenth-century political thought and undermines its power as a foundation for political critique by civic-minded anti-corruption reformers.